Caribbean and Pacific Islands : A Survey of Gender Budgeting Efforts - Christie, Tamoya (IMF Working Papers; Working Paper ;, 2016)
Of the countries in the Caribbean and Pacific Islands, Timor-Leste has the most well-developed gender budgeting initiative. In the Pacific Islands, a few gender budgeting efforts were initiated but did not continue. In the Caribbean, there have been no well-developed gender budgeting efforts, although governments have undertaken policies to promote gender equality. We provide a number of recommendations to improve the effectiveness of gender budgeting efforts. Governments should link gender budgeting to national development plans, set realistic time expectations for achieving results, engage in capacity building with officials, draw upon strengths outside the government, and strengthen regional coordination.